Agency and Evidentiality under English Dominance in Russian and Uzbek News Translation - Satibaldiyev, Erkinjon Kamilovich (The Lingua Spectrum, 2026)
This article examines how English-source news discourse changes when it is translated for Russian and Uzbek readers. The study focuses on two compact but influential zones of journalistic language: agency and evidentiality. A controlled mini-corpus of three Reuters headlines from 2024 was used as analytical material, and Russian and Uzbek newsroom-style renditions were produced for comparison. The analysis shows that English tends to compress agency, delay source attribution, and package evaluation into short headline formulas. Russian usually tolerates this compression more easily and often preserves institutional shorthand. Uzbek more often expands the structure, restores explicit actors, and marks the source of information earlier. These shifts are not random stylistic choices. They reflect asymmetrical linguistic prestige in a plurilingual media environment and the need to rebalance clarity, authority, and reader processing effort. The article argues that pragmatic equivalence in news translation is achieved not through lexical mirroring, but through controlled redistribution of who acts, who knows, and who is named.